Dental Erosions - J. Morozova (Czech Dental Chamber, 2011)
The content of this review is description of dental erosions's clinical picture depending on their different stages, as well as the review of modern diagnostics of dental erosions. Basic Erosive Wear Examination system has been created by Bartlett et al. in 2008. It is a new screening system which can enable the dental erosions diagnostics of particular patients. This easy index may be integrated to everyday dental practice. Risk factor analysis and differential diagnosis are essential part of examination algorithm. In spite of efforts diagnosis of dental erosions is still a complicated and sometimes neglected problem in dentistry. The aim of our review is to determine and describe therapeutical and preventive measures for erosive tooth wear depending on their stages and etiology.